RF-bunching of relativistic 12C3+ ion beam for laser cooling experiment at the CSRe. (29th January 2015) - Wang, H B; Wen, W Q; Ma, X; Huang, Z K; Zhang, D C; Bussmann, M; Winters, D F A; Yuan, Y J; Zhu, X L; Zhao, D M; Mao, R S; Li, J; et al.
Abstract: To prepare the upcoming experiment of laser cooling of relativistic 12 C 3+ ion beams at the experimental cooler storage ring (CSRe), a test experiment was performed with 12 C 3+ ion beams at an energy of 122 MeV/u on the CSRe, at the Institute of Modern Physics, Lanzhou, China. In this experiment, the main storage ring of CSRm was employed to accumulate and accelerate the ion beam which was injected into the CSRe for the experiments. The number of 12 C 3+ ions at the CSRe reached 5×10 8 for every injection, which satisfied the experimental requirement. To fulfil the laser cooling experiment, the 12 C 3+ ion beams were bunched by sinusoidal waveforms with fixed and sweeping frequencies, respectively. A resonant Schottky pick-up was employed to record the Schottky spectra of these ion beams. The test experimental results demonstrated that the RF-buncher and diagnostic systems at the CSRe worked well and the CSRe was very stable with 12 C 3+ ion beams, hereby the CSRe is suitable for laser cooling experiment.